Common genetic variants in the immunoglobulin heavy chain locus and their differential impact on group A streptococcal disease susceptibility: a comparative meta-analysis of genetic susceptibility studies. (23rd February 2017) - Parks, Tom; Auckland, Kathryn; Rautanen, Anna; Watson, Corey; Mirabel, Mariana M; Kado, Joseph; Kauwe, John K; Lamagni, Theresa L; Mentzer, Alexander J; Sriskandan, Shiranee; Thomas, Matthew; Chapman, Stephen; et al.
Abstract: Background: Globally the diverse diseases associated with Streptococcus pyogenes infection are an important public health concern. Building on our recent discovery of a putative rheumatic heart disease susceptibility signal in the immunoglobulin heavy chain locus (IGH), we sought to identify variants in this poorly understood locus with shared and opposing effects on susceptibility to S pyogenes diseases focusing on rheumatic heart disease and invasive S pyogenes, which have mutually exclusive clinical phenotypes. Methods: We conducted a comparative meta-analysis of our genome-wide association studies of susceptibility to rheumatic heart disease and invasive S pyogenes . Patients with rheumatic heart disease were recruited in Fiji, New Caledonia, and Samoa, and patients with invasive S pyogenes in the UK, Kenya, and New Caledonia. Controls were drawn from the same populations with additional controls for the rheumatic heart disease study from other Pacific Island nations. We searched for shared and opposing IGH loci using z-scores from the underlying analyses and used multinominal logistic regression to estimate effect sizes. Findings: After quality control, there were 1028 cases and 2057 controls in the rheumatic heart disease study and 147 cases and 3003 controls in the invasive S pyogenes study with an overlap of 1669 common variants in the IGH locus. We identified a shared effect signal 3·4 kb upstream from the IGHV1-69 gene segment overlapping a putative transcription factor binding site and an opposing effect signal peaking at a missense variant in the second exon of the IGHV1-69 gene segment corresponding to the IGHV3-66*03 allele. After conditioning on the IGHV4-61*02 allele, which we have previously found associated with rheumatic heart disease, the lead shared effect single nucleotide polymorphism (SNP) (rs28627956) conferred increased risk of invasive S pyogenes but with negligible effect on risk of rheumatic heart disease (odds ratio 1·45 [95% CI 1·16–1·73] and 1·06 [0·87–1·24], respectively), whereas the lead opposing effect SNP (rs6423677) conferred reduced risk of invasive S pyogenes (0·75, 0·61–0·96) and increased risk of rheumatic heart disease (1·15, 0·98–1·38). Interpretation: Germline IGH polymorphism is predicted to modify infectious and autoimmune disease susceptibility, although robust examples of such effects are scarce. Our results suggest that such polymorphism might have differential effects on susceptibility to S pyogenes disease, plausibly through coding and regulatory mechanisms. Our results provide new insight into the pathogenesis of these two neglected diseases as well as into the complex interplay between infectious and inflammatory disease. Funding: British Heart Foundation, British Medical Association, European Society of Clinical Microbiology and Infectious Diseases, UK Medical Research Council, Wellcome Trust.